Magnetic Fields in Massive Star-forming Regions (MagMaR). IV. Tracing the Magnetic Fields in the O-type Protostellar System IRAS 16547–4247 - Zapata, Luis A. (2024)
The formation of the massive stars, and in particular, the role that the magnetic fields play in their early evolutionary phase is still far from being completely understood. Here, we present the Atacama Large Millimeter/submillimeter Array 1.2 mm full polarized continuum and H13CO+(3‑2), CS(5‑4), and HN13C(3‑2) line observations with a high angular resolution (∼0.″4 or 1100 au). In the 1.2 mm continuum emission, we reveal a dusty envelope surrounding the massive protostars, IRAS16547-E and IRAS16547-W, with dimensions of ∼10,000 au. This envelope has a biconical structure likely carved by the powerful thermal radio jet present in region. The magnetic field vectors follow very well the biconical envelope. The polarization fraction is ∼2.0% in this region. Some of these vectors seem to converge to IRAS 16547-E and IRAS 16547-W, the most massive protostars. Moreover, the velocity fields revealed from the spectral lines H13CO+(3‑2) and HN13C(3‑2) show velocity gradients with a good correspondence with the magnetic fields, which maybe are tracing the cavities of molecular outflows or maybe infalling in some parts. We derived a magnetic field strength in some filamentary regions that goes from 2 to 6.1 mG. We also find that the CS(5‑4) molecular line emission reveals multiple outflow cavities or bow shocks with different orientations, some of which seem to follow the NW–SE radio thermal jet.